Pengaruh Pelatihan dan Pengembangan SDM Terhadap Kinerja Pegawai Pada Dinas Tenaga Kerja Kota Samarinda - Ni Luh Putri Apriliyani; Sofia Ulfa Eka Hadiyanti; Vera Anitra (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This research examines the influence of training and human resource development on employee performance at theSamarinda City Manpower Service. This study was motivated by a lack of awareness of training and development of human resources for work in the field, so that the training received by the workforce was less than optimal. Data was obtained by distributing questionnaires to 60 employees using a simple random sampling method and analyzed using multiple linear regression via SPSS version 29. The results of the study showed that training had a significant negative effect on employee performance due to inappropriate methods, irrelevant material, and incompetent instructors. Meanwhile, human resource development has a significant positive effect because it is carried out in a structured manner through competency-based division of tasks, advanced training and ongoing coaching. Overall, HR training and development contributed 29% to the variation in employee performance. These findings empha